we know that
If a ordered pair (x,y) is a solution of the equation, then the ordered pair must satisfy the equation
we have the equation
![7x-5y=28](https://tex.z-dn.net/?f=7x-5y%3D28)
Let's verify all the cases to determine the solution to the problem.
<u>case A)</u> point ![(-6,-14)](https://tex.z-dn.net/?f=%28-6%2C-14%29)
Substitute the values of x and y in the equation
![x=-6\\y=-14](https://tex.z-dn.net/?f=x%3D-6%5C%5Cy%3D-14)
![7(-6)-5(-14)=28](https://tex.z-dn.net/?f=7%28-6%29-5%28-14%29%3D28)
![-42+70=28](https://tex.z-dn.net/?f=-42%2B70%3D28)
-------> is true
therefore
The point
is a solution of the equation
<u>case B)</u> point ![(-1,-7)](https://tex.z-dn.net/?f=%28-1%2C-7%29)
Substitute the values of x and y in the equation
![x=-1\\y=-7](https://tex.z-dn.net/?f=x%3D-1%5C%5Cy%3D-7)
![7(-1)-5(-7)=28](https://tex.z-dn.net/?f=7%28-1%29-5%28-7%29%3D28)
![-7+35=28](https://tex.z-dn.net/?f=-7%2B35%3D28)
-------> is true
therefore
The point
is a solution of the equation
<u>case C)</u> point ![(4,10)](https://tex.z-dn.net/?f=%284%2C10%29)
Substitute the values of x and y in the equation
![x=4\\y=10](https://tex.z-dn.net/?f=x%3D4%5C%5Cy%3D10)
![7(4)-5(10)=28](https://tex.z-dn.net/?f=7%284%29-5%2810%29%3D28)
![28-50=28](https://tex.z-dn.net/?f=28-50%3D28)
-------> is not true
therefore
The point
is not a solution of the equation
<u>case D)</u> point ![(7,9)](https://tex.z-dn.net/?f=%287%2C9%29)
Substitute the values of x and y in the equation
![x=7\\y=9](https://tex.z-dn.net/?f=x%3D7%5C%5Cy%3D9)
![7(7)-5(9)=28](https://tex.z-dn.net/?f=7%287%29-5%289%29%3D28)
![49-45=28](https://tex.z-dn.net/?f=49-45%3D28)
-------> is not true
therefore
The point
is not a solution of the equation
therefore
<u>the answer is </u>
![(-6,-14)](https://tex.z-dn.net/?f=%28-6%2C-14%29)
![(-1,-7)](https://tex.z-dn.net/?f=%28-1%2C-7%29)
Let's look at an example:
2.24 x 21.6
![2.24\\ 21.6\\ ______](https://tex.z-dn.net/?f=2.24%5C%5C%2021.6%5C%5C%20______)
Do normal multiplication and get
48384 This is not correct, until we put the decimals in. To know how to do this, count the number of decimal spaces from the factors. In 2.24, there are 2, because .24. In 21.6 there are 1 because of .6. This mean three places, so 48384 becomes
48.384
~theLocoCoco
We are told that the first term is 2. The next term is 7(2) = 14; the third term is 7(14) = 98. And so on. So, the first term and the common ratio (7) are known.
The nth term of this geometric series is a_n = 2(7)^(n-1).
Check: What is the first term? We expect it is 2. 2(7)^(1-1) = 2(1) = 2. Correct.
What is the third term? We expect it is 98. 2(7)^(3-1) = 2(7)^2 = 98. Right.<span />
Answer:
the answer is c i took the quiz
Step-by-step explanation:
Answer:
it is b
Step-by-step explanation: